Patterns of co-occurring comorbidities in people living with HIV - Francesco,DD; Verboeket,SO; Underwood,J; Bagkeris,E; Wit,FW; Mallon,PWG; Winston,A; Reiss,P; Sabin,CA; Pharmacokinetic,and Clinical Observations in PeoPle Over fiftY POPPY study and the AGEhIV Cohort Study (Open Forum Infectious Diseases, 2018)
Background: The aims of this study were to identify common patterns of comorbidities observed in people living with HIV (PLWH), using a data-driven approach, and evaluate associations between patterns identified. Methods: A wide range of comorbidities were assessed in PLWH participating in 2 independent cohorts (POPPY: UK/Ireland; AGEhIV: Netherlands). The presence/absence of each comorbidity was determined using a mix of self-reported medical history, concomitant medications, health care resource use, and laboratory parameters. Principal component analysis (PCA) based on Somers' D statistic was applied to identify patterns of comorbidities. Results: PCA identified 6 patterns among the 1073 POPPY PLWH (85.2% male; median age [interquartile range IQR], 52 [47-59] years): cardiovascular diseases (CVDs), sexually transmitted diseases (STDs), mental health problems, cancers, metabolic disorders, chest/other infections. The CVDs pattern was positively associated with cancer (r = .32), metabolic disorder (r = .38), mental health (r = .16), and chest/other infection (r = .17) patterns (all P < .001). The mental health pattern was correlated with all the other patterns (in particular cancers: r = .20; chest/other infections: r = .27; both P < .001). In the 598 AGEhIV PLWH (87.6% male; median age [IQR], 53 [48-59] years), 6 patterns were identified: CVDs, chest/liver, HIV/AIDS events, mental health/neurological problems, STDs, and general health. The general health pattern was correlated with all the other patterns (in particular CVDs: r = .14; chest/liver: r = .15; HIV/AIDS events: r = .31; all P < .001), except STDs (r = -.02; P = .64). Conclusions: Comorbidities in PLWH tend to occur in nonrandom patterns, reflecting known pathological mechanisms and shared risk factors, but also suggesting potential previously unknown mechanisms. Their identification may assist in adequately addressing the pathophysiology of increasingly prevalent multimorbidity in PLWH.